Victoria Ocampo’s gift for world culture - United Nations Educational, Scientific; Cultural Organization; Jacques Rigaud (The UNESCO Courier, 2023)
On 15 January 1973, Mme Victoria Ocampo and her sister Mme Angelica Ocampo, of Argentina, donated to UNESCO a group of estates including the spacious Villa Ocampo at San Isidro, Buenos Aires. In accordance with the wishes of its donor, Victoria Ocampo, the villa will be used “for promotion, research, experimentation and development of activities related to culture, literature, art and social communication, which are aimed at improving the quality of human life “ The villa is particularly appropriate as a setting for “permanent studios or for programmes of research, experimentation or production related to the cinema, television, theatre, music and literature, for translation or new forms of expression and communication, as well as new types and techniques of cultural and artistic creation and art education.”